A qualitative study of attachment relationships in ASD during middle childhood. Issue 1 (2nd January 2017) - Keenan, Belinda M; Newman, Louise K; Gray, Kylie M; Rinehart, Nicole J
ABSTRACT: Although research has indicated that children with Autism Spectrum Disorder (ASD) display normative attachment behaviours, to date there has been limited qualitative research exploring these relationships. This study aimed to describe qualitative features of the child–caregiver attachment relationship in children with ASD. Primary caregivers to 26 children with ASD (aged 7–14 years) and 23 typically developing children (aged 7–13 years) were administered the Disturbances of Attachment Interview (Smyke & Zeanah, 1999) to elicit descriptions of children's attachment behaviours. Thematic analysis of interview transcripts indicated that while children with ASD demonstrated a range of normative attachment behaviours, they displayed impairments in the use of the caregiver as a secure base and co-regulating agent. ASD-associated impairments in emotion processing, sharing/reciprocity, and emotion co-regulation, as well as the caregiver's experience, were important in understanding attachment relationships in ASD. Findings highlight the need to consider the bidirectional nature of the attachment relationship in ASD.